2000
DOI: 10.1017/s0022112000008909
|View full text |Cite
|
Sign up to set email alerts
|

New results in rotating Hagen–Poiseuille flow

Abstract: New three-dimensional finite-amplitude travelling-wave solutions are found in rotating Hagen–Poiseuille flow (RHPF[Ωa, Ωp]) where fluid is driven by a constant pressure gradient along a pipe rotating axially at rate Ωa and at Ωp about a perpendicular diameter. For purely axial rotation (RHPF[Ωa, 0]), the two-dimensional helical waves found by Toplosky & Akylas (1988) are found to become unstable to three-dimensional travelling waves in a supercritical Hopf bifurcation. The addition of a perpendicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…The existence of exact coherent states in pipe flow has been an object of speculation for some time [7,12,19] but different earlier attempts to find them numerically have failed [3,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of exact coherent states in pipe flow has been an object of speculation for some time [7,12,19] but different earlier attempts to find them numerically have failed [3,44].…”
Section: Discussionmentioning
confidence: 99%
“…Barnes & Kerswell [3] investigated in travelling waves in rotating pipe flow where fluid is driven by a constant pressure gradient along a pipe which is rotating axially as well as about a perpendicular diameter, i.e. a rotating and precessing pipe.…”
Section: Earlier Attempts To Find Coherent States In Pipe Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…5 appeared as a plausible alternative to the centrifugal instability approach in order to identify a self-sustaining process at R Ω = −1. Such an attempt was further encouraged by the work of Wedin & Kerswell (2004), who managed to identify a self-sustaining process in non-rotating pipe Poiseuille flow by continuing forced nonlinear solutions, whereas Barnes & Kerswell (2000) had previously been unable to continue nonlinear solutions obtained for a rotating pipe Poiseuille flow down to zero rotation.…”
Section: Pitfalls Of the Forcing Approachmentioning
confidence: 99%
“…This has been successful in other cases [13,15,16]. For pipe flow Barnes and Kerswell [23] showed that the instabilities that arise from rotation do not extend to the case of pure pipe flow. Guided by the dominance of downstream vortices in the stationary and travelling states in planar shear flows we therefore adopted the following strategy, similar to the one used in [14]: at low Reynolds number a volume force F that generates a transverse flow with translation invariant downstream vortices was added.…”
mentioning
confidence: 97%